The relationship between job demands, job resources and work engagement: a study among employees at department of agriculture, Putrajaya - Farah Amiera, Abu Bakar (2020)
Good work engagement among employees is very crucial to ensure employees are engaged with their job in order to achieve an organizational success. The purpose of this study is to examine the relationship between job demands (workload and work-family conflicts), job resources (social support, performance feedback and organizational culture) and work engagement among employees at Department of Agriculture, Putrajaya. 300 respondents have participated in this research. This research used survey method using questionnaire and analysed by descriptive analysis, factor analysis, reliability test, Pearson correlation analysis and multiple regression analysis by using statistical package for social sciences (SPSS). Findings showed that there is no relationship between workload with work engagement, while work-family conflict have moderate strength negatively relationship with work engagement. The results also showed that the other variables such as social support, performance feedback and organizational culture have moderate strength positively relationship with work engagement. In a nutshell, discussion and conclusion on the implication of this research were presented.